Analisis Penggunaan Serbuk Kaca Dan Pecahan Keramik Terhadap Kuat Tekan Dan Kuat Lentur Beton - Danusaputra, Maraya; Setiawan, Arman; Yunus, Ahmad Yauri (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
In the current technological era, concrete is one of the most widely used building materials in the world, including in Indonesia, therefore good quality concrete will greatly support structural safety. Indonesia is also a developing country that has quite advanced industrial prospects. Glass waste and ceramic waste are increasing in volume every day because many human activities produce glass and ceramics. Most of the glass and ceramic waste is directly disposed of in open areas. This of course will pollute the environment, considering that glass and ceramics are non-recyclable materials. naturally repeated by nature. This study aims to reduce the impact caused by waste glass and ceramic shards that are disposed of directly into nature. By using word powder as a partial replacement for fine aggregate (sand) at a constant 10%, and using ceramic shards as a partial replacement for coarse aggregate at 30%, 40%, and 50%, the compressive strength results are 21.02 MPa, 21.31 MPa, and 26.21 MPa. And the resulting flexural strength is 3.87 MPa, 3.87 MPa, and 3.60 MPa.